وحدتِ اُمت کے قرآنی و نبوی اصول: عصری تناظر میں تجزیاتی مطالعہ: (THE QUR’ANIC AND PROPHETIC PRINCIPLES OF MUSLIM UNITY: AN ANALYTICAL STUDY IN CONTEMPORARY PERSPECTIVE) (Al-Aasar, 2026)
The unity of the Muslim Ummah stands as one of the central objectives of the Qur’anic revelation and Prophetic mission, reflecting Islam’s vision of a morally cohesive and spiritually enlightened global community. The Qur’an repeatedly exhorts believers to adhere collectively to the rope of Allah (ḥabl Allāh) and forbids division, emphasizing that the strength of faith and civilization rests upon mutual harmony, justice, and compassion. Likewise, the Prophetic Sunnah provides a living model of unity, wherein diversity of opinion coexists with shared moral purpose and collective responsibility. This research undertakes an analytical and critical study of the Qur’anic and Prophetic principles of Muslim unity within the contemporary socio-political and intellectual context.Adopting a qualitative, descriptive, and interpretative methodology, the study draws upon Qur’anic exegesis, Hadith scholarship, and classical juristic thought, supplemented by modern Islamic intellectual discourse. It critically explores the ethical and epistemological foundations of unity, identifying factors such as sectarianism, nationalism, and political fragmentation as key challenges undermining the spirit of ukhuwwah islāmiyyah (Islamic brotherhood). The paper argues that authentic Muslim unity does not lie in uniformity of jurisprudential views or political systems but in the realization of shared divine values; justice (ʿadl), compassion (raḥmah), and piety (taqwā).The findings underscore that the revival of Muslim solidarity in the twenty-first century demands a paradigm shift from ideological rigidity to intellectual dialogue, from sectarian exclusivism to ethical inclusivity, and from mere rhetoric to actionable cooperation in education, governance, and global representation. Hence, Qur’anic wisdom and Prophetic guidance collectively offer a timeless and comprehensive framework for re-establishing unity, peace, and dignity among the nations of Islam.